STRATEGI PENGEMBANGAN KAWASAN CITYWALK JALAN MERAK KOTA SEMARANG - Primandaru, Ganjar (Jurnal Tataloka, 2009)
City Walk area is expected to become new activities centre for the community in Semarang as well as to maximize itsfunction and potentials, and to improve Kota Lama area as a heritage area. This research aims to formulate strategy of City Walkarea development by using qualitative approach and applying descriptive method, frequency distribution method, and SWOT matrixanalysis. The results show that the development of City Walk area has beneficial position according to Strategic Advantage Profile(SAP) and is regarded as an optimal effort according to Environmental Threat and Opportunity Profile (ETOP) matrix. Based onthose positions, the development of City Walk area has prospective opportunity requiring the right strategies. According to SWOTanalysis matrix, the right development strategies consist of three strategies that are development strategy of tourism component,which is tourism attractions; development strategy of physical aspect, and development strategy of area management. This researchsuggests that the development of City Walk district is strongly related to the existing buildings around the corridor. Therefore, theneeds of development require building owner participation in order to implement the revitalization successful.STRATEGI PENGEMBANGAN KAWASAN CITYWALKJALAN MERAK KOTA SEMARANG